Determination method of styrene polymer in polyolefin-styrene polymer blend system

Through the Py-GCMS test method, thermal cracking and gas chromatography coupled with mass spectrometry technology are used to quickly distinguish the hydrogenation type of SEBS in the polyolefin-SEBS blend system, solving the problems of difficulty in differentiation and unenvironmental protection of the method in the existing technology, and realizing to achieve efficient and accurate test results.

CN119147670BActive Publication Date: 2025-01-21GUANGZHOU LUSHAN NEW MATERIALS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411640799.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-21
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately distinguish the hydrogenation type of SEBS in the polyolefin-SEBS blending system. The traditional methods and equipment are expensive, costly to use, and the pre-treatment process is cumbersome, and the use of toxic chemical solvents is required. The test results have many interfering factors.

Method used

Using the Py-GCMS test method, the thermal cracking temperature is 550°C to 650°C, m/z 104 and m/z 168 are selected as characteristic ions, the corresponding ion chromatogram is extracted, the peaks are analyzed, and the styrene in the blend system is distinguished. Types of polymeroids.

Benefits of technology

It is possible to quickly distinguish the types of polystyrene polymers blended with polyolefins. The method is green, environmentally friendly, accurate and efficient, and avoids the problems of high equipment costs and cumbersome pre-treatment of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119147670B_ABST
    Figure CN119147670B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of detection and analysis technology, and in particular to a method for determining styrene polymers in a polyolefin-styrene polymer blend system, comprising the following steps: (a) subjecting the sample to be tested to a Py-GCMS test, selecting m / z 104 and m / z 168 as characteristic ions, and extracting the corresponding ion flow diagram; (b) analyzing the types of styrene polymers in the blend system according to the peak conditions in the ion flow diagram; the thermal cracking temperature in the test is 550°C to 650°C; in the blend system, the mass percentage of styrene polymers is 10% to 100%. The present invention utilizes the cracking principle of styrene polymers of different structures at high temperatures and understands the difference in products, and can quickly distinguish the types of polystyrene polymers blended with polyolefins, and the method is green, environmentally friendly, accurate and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of detection and analysis, and in particular to a method for determining styrene polymers in a polyolefin-styrene polymer blend system. Background Art

[0002] Hydrogenated styrene-butadiene-styrene block copolymer (SEBS) has excellent mechanical properties, is non-toxic and environmentally friendly, and has good chemical properties. It is often used in polyolefin blending systems such as polypropylene and polyethylene to improve the compatibility of the blends. Polyolefin-SEBS blending systems have been widely used in plastic modification, adhesives, wires and cables, engineering plastics modification and other fields.

[0003] When polystyrene, 1,2 addition SEBS or 1,4 addition SEBS are added to polyolefin, the corresponding product performance will show obvious differences. When the raw materials need to be verified for composition, it becomes very important to quickly detect the hydrogenation type of SEBS in the polyolefin-SEBS blend system. In addition, when the product has abnormal performance or failure, it is necessary to analyze the cause. Rapidly and accurately testing the hydrogenation type of SEBS in the polyolefin-SEBS blend system can help locate the problem and seek a better solution.

[0004] Nuclear magnetic resonance can be used to identify the hydrogenation type of SEBS in a polyolefin-SEBS blend system, but the equipment is expensive and has a high cost of use. In addition, the sample to be tested must be completely dissolved before testing to separate the polyolefin in the sample. The pretreatment process is cumbersome and requires the use of toxic chemical solvents, and there are many interference factors in the test results.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a method for determining styrene polymers in a polyolefin-styrene polymer blend system, which can quickly distinguish the types of styrene polymers blended with polyolefins and is green, environmentally friendly, accurate and efficient.

[0007] In order to achieve the above-mentioned object of the present invention, the present invention provides a method for determining styrene polymers in a polyolefin-styrene polymer blend system, comprising the following steps:

[0008] (a) The blended system sample to be tested was subjected to Py-GCMS test, m / z 104 and m / z 168 were selected as characteristic ions, and the corresponding ion chromatograms were extracted;

[0009] (b) analyzing and obtaining the type of styrene polymer in the blend system according to the peaks in the ion flow diagram corresponding to m / z 104 and m / z 168;

[0010] In the test, the thermal cracking temperature is 550°C to 650°C;

[0011] In the blending system, the mass percentage of the styrene polymer is 10% to 100%.

[0012] In a specific embodiment of the present invention, in the blending system, the styrene polymer includes any one of polystyrene and SEBS. Further, the SEBS includes any one of 1,2 addition SEBS and 1,4 addition SEBS.

[0013] In a specific embodiment of the present invention, in the blending system, the polyolefin includes at least one of high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), metallocene linear low-density polyethylene (MVLLDPE), polyolefin elastomer (POE) and polypropylene (PP).

[0014] In a specific embodiment of the present invention, in the test, the thermal cracking time is 10s to 30s.

[0015] In a specific embodiment of the present invention, the test conditions also include:

[0016] The chromatographic column model is HP-5MS; the split ratio is (100-200) : 1; the interface temperature is 280℃-300℃, and the front injection port temperature is 280℃-300℃;

[0017] The GC temperature program was as follows: after keeping at 40°C for 2 min, the temperature was increased to 300°C at 20°C / min, and then kept at 300°C for 10 min.

[0018] In a specific embodiment of the present invention, the mass of the sample is 0.1 mg to 0.5 mg.

[0019] In a specific embodiment of the present invention, the analysis includes: when a peak appears at a retention time of 5.07min±0.1min in the ion flow chart of m / z 104, and there are no double peaks at retention times of 7.14min±0.1min and 7.67min±0.1min in the ion flow chart of m / z 168, then the styrene polymer in the blending system is polystyrene.

[0020] In a specific embodiment of the present invention, the analysis includes: when the peak at the retention time of 5.07min±0.1min appears in the ion flow diagram of m / z 104, and there are double peaks at the retention times of 7.14min±0.1min and 7.67min±0.1min in the ion flow diagram of m / z 168, the styrene polymer in the blending system is SEBS. Further, the analysis also includes: integrally calculating the peak areas at the retention times of 7.14min±0.1min and 7.67min±0.1min in the ion flow diagram of m / z 168, which are S1 and S2 respectively; when the ratio of S1 to S2 satisfies: 1<S1 / S2<4, the styrene polymer in the blending system is 1,2 addition SEBS; when the ratio of S1 to S2 satisfies: 0.2<S1 / S2<1, the styrene polymer in the blending system is 1,4 addition SEBS.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention utilizes the cracking principle of styrene polymers with different structures at high temperature and understands the difference in products, and can quickly distinguish the types of polystyrene polymers blended with polyolefins. The method is green, environmentally friendly, accurate and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 The total ion current diagram of thermal cracking of polystyrene, 1,2 addition SEBS, 1,4 addition SEBS and HDPE provided in the embodiments of the present invention;

[0025] Figure 2 Ion flow diagram of characteristic ion m / z 104 of polystyrene, 1,2 addition SEBS, 1,4 addition SEBS and HDPE provided in the embodiments of the present invention;

[0026] Figure 3 Ion chromatograms of characteristic ions m / z 168 of polystyrene, 1,2 addition SEBS, 1,4 addition SEBS and HDPE provided in embodiments of the present invention;

[0027] Figure 4 The ion flow diagram of the characteristic ion m / z 104 of the blending system sample to be tested and HDPE in Example 1 of the present invention;

[0028] Figure 5 The ion flow diagram of the characteristic ion m / z 168 of the blending system sample to be tested and HDPE in Example 1 of the present invention;

[0029] Figure 6 The ion flow diagram of the characteristic ion m / z 104 of the blending system sample to be tested and HDPE in Example 2 of the present invention;

[0030] Figure 7 The ion flow diagram of the characteristic ion m / z 168 of the blending system sample to be tested and HDPE in Example 2 of the present invention;

[0031] Figure 8 The ion flow diagram of the characteristic ion m / z 104 of the blended system sample to be tested and POE in Example 3 of the present invention;

[0032] Fig. 9 The ion flow diagram of the characteristic ion m / z 168 of the blended system sample to be tested and POE in Example 3 of the present invention;

[0033] Fig.10 The ion flow diagram of the characteristic ion m / z 104 of the blended system sample to be tested and POE in Example 4 of the present invention;

[0034] Fig.11 The ion flow diagram of the characteristic ion m / z 168 of the blended system sample to be tested and POE in Example 4 of the present invention;

[0035] Fig.12 The ion flow diagram of the characteristic ion m / z 104 of the blending system sample to be tested and PP in Example 5 of the present invention;

[0036] Fig.13 The ion flow diagram of the characteristic ion m / z 168 of the blending system sample to be tested and PP in Example 5 of the present invention;

[0037] Fig.14 The ion flow diagram of the characteristic ion m / z 104 of the blending system sample to be tested and PP in Example 6 of the present invention;

[0038] Fig.15 The ion flow diagram of the characteristic ion m / z 168 of the blending system sample to be tested and PP in Example 6 of the present invention;

[0039] Fig.16 The ion flow diagram of the characteristic ion m / z 104 of the blending system sample to be tested and HDPE in Example 7 of the present invention;

[0040] Fig.17The ion flow diagram of the characteristic ion m / z 168 of the blending system sample to be tested and HDPE in Example 7 of the present invention;

[0041] Fig.18 The ion flow diagram of the characteristic ion m / z 104 of the blending system sample to be tested and HDPE in Comparative Example 1 of the present invention;

[0042] Fig.19 The ion flow diagram of the characteristic ion m / z 168 of the blending system sample to be tested and HDPE in Comparative Example 1 of the present invention;

[0043] Fig. 20 The ion flow diagram of the characteristic ion m / z 104 of the blending system sample to be tested and PP in Comparative Example 3 of the present invention;

[0044] Fig.21 It is the ion flow diagram of the characteristic ion m / z 168 of the blending system sample to be tested in Comparative Example 3 of the present invention and PP. DETAILED DESCRIPTION

[0045] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0046] The present invention utilizes the different structures of SEBS and polystyrene (PS) and the different cracking principles and products of SEBS of different hydrogenation types at high temperature, and uses thermal cracking-gas chromatography-mass spectrometry to quickly determine the styrene polymer in the blending system.

[0047] The present invention provides a method for determining styrene polymers in a polyolefin-styrene polymer blend system, comprising the following steps:

[0048] (a) The blended system sample to be tested was subjected to Py-GCMS test, m / z 104 and m / z 168 were selected as characteristic ions, and the corresponding ion chromatograms were extracted;

[0049] (b) Based on the peaks in the ion flow diagram corresponding to m / z 104 and m / z 168, the types of styrene polymers in the blending system were analyzed;

[0050] In the test, the thermal cracking temperature was 550°C to 650°C;

[0051] In the blending system, the mass percentage of the styrene polymer is 10% to 100%.

[0052] PS is directly cracked into styrene monomer at high temperature. 1,2 addition SEBS and 1,4 addition SEBS are cracked at high temperature to form styrene monomer. In addition, olefin trimers with different branched structures are formed through free radical generation and chain rearrangement. By comparing the retention time and peak area of ​​olefin trimers, 1,2 addition SEBS, 1,4 addition SEBS and PS blended with polyolefins can be quickly distinguished, which is green, environmentally friendly, accurate and efficient.

[0053] Figure 1 This is the total ion current diagram of thermal decomposition of polystyrene, 1,2 addition SEBS, 1,4 addition SEBS and HDPE. Figure 2 The ion chromatograms of characteristic ions m / z 104 of polystyrene, 1,2 addition SEBS, 1,4 addition SEBS and HDPE are shown in Figure 1. Figure 3 The ion chromatograms of characteristic ions m / z 168 of polystyrene, 1,2 addition SEBS, 1,4 addition SEBS and HDPE. The retention time 5.07min corresponds to the peak time of the characteristic ion of styrene monomer, the retention time 7.14min corresponds to the peak time of the characteristic ion of 2,4,6-triethylhexene, and the retention time 7.67min corresponds to the peak time of the characteristic ion of 2-methyl-undecene. It can be seen that the ion chromatogram of the characteristic ion m / z 104 is extracted, and the characteristic ion of m / z 104 cannot be formed after polyolefin pyrolysis, so polyolefin, polyolefin-PS or polyolefin-SEBS can be distinguished. The ion chromatogram of the characteristic ion m / z 168 is extracted, and since polyolefin-PS cannot form double peaks at retention times 7.14min and 7.67min after pyrolysis, polyolefin-PS and polyolefin-SEBS can be distinguished. The double peaks at retention times of 7.14 min and 7.67 min in the ion flow chart of the characteristic ion m / z 168 were integrated separately, and the hydrogenation type of SEBS was distinguished based on the peak area ratio.

[0054] For example, in different embodiments, in the Py-GCMS test, the temperature of thermal cracking can be 550° C., 580° C., 600° C., 620° C., 650° C., or a range consisting of any two thereof.

[0055] For example, in different embodiments, in the blending system, the mass percentage of the styrene-based polymer can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 99%, 100% or a range consisting of any two thereof.

[0056] In actual operation, in the sample of the blending system to be tested, the blending method of polyolefin and styrene polymer is not limited, and the two substances can be mixed above the melting point in a certain proportion. For example, the mixture can be mixed and kneaded at 180-195°C for 4-10 minutes. This is not to limit the blending method of the polyolefin-styrene polymer to be tested, but only an optional blending method. As long as the polyolefin-styrene polymer blend system to be tested is obtained by blending polyolefin and styrene polymer, the determination method of the present invention can be used.

[0057] In a specific embodiment of the present invention, in the blending system, the styrene polymer includes any one of polystyrene and SEBS. Further, the SEBS includes any one of 1,2 addition SEBS and 1,4 addition SEBS.

[0058] In a specific embodiment of the present invention, in the blending system, the polyolefin includes at least one of high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), metallocene linear low-density polyethylene (MVLLDPE), polyolefin elastomer (POE) and polypropylene (PP).

[0059] In a specific embodiment of the present invention, in the test, the thermal cracking time is 10s to 30s. For example, in different embodiments, the thermal cracking time can be 10s, 15s, 20s, 25s, 30s or a range consisting of any two thereof.

[0060] In a specific embodiment of the present invention, the test conditions also include:

[0061] The chromatographic column model is HP-5MS; the split ratio is (100-200) : 1; the interface temperature is 280℃-300℃, and the front injection port temperature is 280℃-300℃;

[0062] The GC temperature program was as follows: after keeping at 40°C for 2 min, the temperature was increased to 300°C at 20°C / min, and then kept at 300°C for 10 min.

[0063] For example, in different embodiments, under the test conditions, the split ratio can be 100:1, 120:1, 150:1, 180:1, 200:1 or a range consisting of any two thereof; the interface temperature can be 280°C, 290°C, 300°C or a range consisting of any two thereof; the front inlet temperature can be 280°C, 290°C, 300°C or a range consisting of any two thereof.

[0064] The parameters not mentioned in the Py-GCMS test are all conventional parameter settings.

[0065] In a specific embodiment of the present invention, the mass of the sample is 0.1 mg to 0.5 mg.

[0066] For example, in different embodiments, the sample is placed in a Py-GCMS pyrolysis instrument, and the specific mass of the sample can be 0.1 mg, 0.2 mg, 0.3 mg, 0.4 mg, 0.5 mg, or a range consisting of any two thereof.

[0067] In a specific embodiment of the present invention, the analysis includes: when a peak appears at a retention time of 5.07min±0.1min in the ion flow chart of m / z 104, and there are no double peaks at retention times of 7.14min±0.1min and 7.67min±0.1min in the ion flow chart of m / z 168, then the styrene polymer in the blending system is PS.

[0068] In a specific embodiment of the present invention, the analysis includes: when the peak at the retention time of 5.07min±0.1min appears in the ion flow diagram of m / z 104, and there are double peaks at the retention times of 7.14min±0.1min and 7.67min±0.1min in the ion flow diagram of m / z 168, the styrene polymer in the blending system is SEBS. Further, the analysis also includes: integrally calculating the peak areas at the retention times of 7.14min±0.1min and 7.67min±0.1min in the ion flow diagram of m / z 168, which are S1 and S2 respectively; when the ratio of S1 to S2 satisfies: 1<S1 / S2<4, the styrene polymer in the blending system is 1,2 addition SEBS; when the ratio of S1 to S2 satisfies: 0.2<S1 / S2<1, the styrene polymer in the blending system is 1,4 addition SEBS.

[0069] The following examples further verify the accuracy and reliability of the determination method of the present invention.

[0070] Example 1

[0071] This embodiment provides a method for determining the hydrogenation type of SEBS in a blend of HDPE and SEBS, comprising the following steps:

[0072] (1) Weigh 90 parts of HDPE material and 10 parts of 1,2 addition SEBS material by weight, mix them in a Haake rheometer at a heating temperature of 190°C and a mixing time of 6 min to obtain a HDPE-SEBS blend.

[0073] (2) Weigh 0.2 mg of the HDPE-SEBS blend obtained in step (1) as a sample and place it in a Py-GCMS pyrolysis instrument. The pyrolysis temperature is set to 600°C and the pyrolysis time is 10 s. The chromatographic column model is HP-5MS. The GC heating program is: retain at 40°C for 2 min, heat to 300°C at 20°C / min, and then retain at 300°C for 10 min. The split ratio is 100:1. The interface temperature is 300°C and the front inlet temperature is 300°C. Obtain the pyrolysis mass spectrum and extract the ion chromatograms with m / z 104 and m / z 168 as characteristic ions, as shown in the figure below. Figure 4 and Figure 5 shown.

[0074] from Figure 4 It can be seen that the HDPE-SEBS blend has an obvious characteristic response of styrene monomer at a retention time of 5.07 min. In addition, in the m / z 168 ion flow chart, the HDPE-SEBS blend has double peaks at retention times of 7.14 min and 7.67 min. 7.14min / S 7.67min =2.7, which can quickly identify that the material blended with HDPE is 1,2 addition SEBS, which is consistent with the actual situation.

[0075] Example 2

[0076] This embodiment provides a method for determining the hydrogenation type of SEBS in a blend of HDPE and SEBS, comprising the following steps:

[0077] (1) 90 parts of HDPE material (same as in Example 1) and 10 parts of 1,4-addition SEBS material were weighed by weight and mixed in a Haake rheometer at a heating temperature of 190° C. for 6 min to obtain a HDPE-SEBS blend.

[0078] (2) Weigh 0.3 mg of the HDPE-SEBS blend obtained in step (1) as a sample and place it in a Py-GCMS pyrolysis instrument. The pyrolysis temperature is set to 600°C and the pyrolysis time is 25 s. The chromatographic column model is HP-5MS. The GC heating program is: retain at 40°C for 2 min, heat to 300°C at 20°C / min, and then retain at 300°C for 10 min. The split ratio is 150:1. The interface temperature is 300°C and the front inlet temperature is 300°C. Obtain the pyrolysis mass spectrum and extract the ion chromatograms with m / z 104 and m / z 168 as characteristic ions, as shown in the figure below. Figure 6 and Figure 7 shown.

[0079] from Figure 6It can be seen that the HDPE-SEBS blend has an obvious characteristic response of styrene monomer at a retention time of 5.07 min. In addition, in the m / z 168 ion flow chart, the HDPE-SEBS blend has double peaks at retention times of 7.14 min and 7.67 min. 7.14min / S 7.67min =0.38, which can quickly identify that the material blended with HDPE is 1,4 addition SEBS, which is consistent with the actual situation.

[0080] Example 3

[0081] This embodiment provides a method for determining the hydrogenation type of SEBS in a POE and SEBS blend system, comprising the following steps:

[0082] (1) Weigh 50 parts of POE material and 50 parts of 1,2 addition SEBS material (same as Example 1) by weight, mix them evenly in a Haake rheometer at a heating temperature of 190° C. for 6 min to obtain a POE-SEBS blend.

[0083] (2) Weigh 0.3 mg of the POE-SEBS blend prepared in step (1) as a sample and place it in a Py-GCMS pyrolysis instrument. The pyrolysis temperature is set to 650°C and the pyrolysis time is 20 s. The chromatographic column model is HP-5MS. The GC heating program is: retain at 40°C for 2 min, increase the temperature to 300°C at 20°C / min, and then retain at 300°C for 10 min. The split ratio is 200:1. The interface temperature is 280°C and the front inlet temperature is 280°C. Obtain the pyrolysis mass spectrum and extract the ion chromatograms with m / z 104 and m / z 168 as characteristic ions, as shown in the figure below. Figure 8 and Fig. 9 shown.

[0084] from Figure 8 It can be seen that the POE-SEBS blend has an obvious characteristic response of styrene monomer at a retention time of 5.07 min. In addition, in the ion flow chart of m / z 168, the POE-SEBS blend has double peaks at retention times of 7.14 min and 7.67 min. 7.14min / S 7.67min =2.8, which can quickly identify that the material blended with POE is 1,2 addition SEBS, which is consistent with the actual situation.

[0085] Example 4

[0086] This embodiment provides a method for determining the hydrogenation type of SEBS in a POE and SEBS blend system, comprising the following steps:

[0087] (1) Weigh 50 parts of POE material and 50 parts of 1,4-addition SEBS material (same as Example 2) by weight, mix them evenly in a Haake rheometer at a heating temperature of 190° C. for 6 min to obtain a POE-SEBS blend.

[0088] (2) Weigh 0.5 mg of the POE-SEBS blend prepared in step (1) as a sample and place it in a Py-GCMS pyrolysis instrument. The pyrolysis temperature is set to 550°C and the pyrolysis time is 25 s. The chromatographic column model is HP-5MS. The GC heating program is: retain at 40°C for 2 min, heat to 300°C at 20°C / min, and then retain at 300°C for 10 min. The split ratio is 200:1. The interface temperature is 290°C and the front inlet temperature is 290°C. Obtain the pyrolysis mass spectrum and extract the ion chromatograms with m / z 104 and m / z 168 as characteristic ions, as shown in the figure below. Fig.10 and Fig.11 shown.

[0089] from Fig.10 It can be seen that the POE-SEBS blend has an obvious characteristic response of styrene monomer at a retention time of 5.07 min. In addition, in the ion flow chart of m / z 168, the POE-SEBS blend has double peaks at retention times of 7.14 min and 7.67 min. 7.14min / S 7.67min =0.37, which can quickly identify that the material blended with POE is 1,4 addition SEBS, which is consistent with the actual situation.

[0090] Example 5

[0091] This embodiment provides a method for determining the hydrogenation type of SEBS in a blend of PP and SEBS, comprising the following steps:

[0092] (1) 10 parts of PP material and 90 parts of 1,2 addition SEBS material (same as in Example 1) were weighed and mixed in a Haake rheometer at a heating temperature of 190° C. for 6 min to obtain a PP-SEBS blend.

[0093] (2) Weigh 0.25 mg of the PP-SEBS blend obtained in step (1) as a sample and place it in a Py-GCMS pyrolysis instrument. The pyrolysis temperature is set to 600°C and the pyrolysis time is 15 s. The chromatographic column model is HP-5MS. The GC heating program is: retain at 40°C for 2 min, heat to 300°C at 20°C / min, and then retain at 300°C for 10 min. The split ratio is 100:1. The interface temperature is 300°C and the front inlet temperature is 300°C. Obtain the pyrolysis mass spectrum and extract the ion chromatograms with m / z 104 and m / z 168 as characteristic ions, as shown in the figure below. Fig.12 and Fig.13 shown.

[0094] from Fig.12 It can be seen that the PP-SEBS blend has an obvious characteristic response of styrene monomer at a retention time of 5.07 min. In addition, in the ion flow chart of m / z 168, the PP-SEBS blend has double peaks at retention times of 7.14 min and 7.67 min. 7.14min / S 7.67min =2.6, which can quickly identify that the material blended with PP is 1,2 addition SEBS, which is consistent with the actual situation.

[0095] Example 6

[0096] This embodiment provides a method for determining the hydrogenation type of SEBS in a blend of PP and SEBS, comprising the following steps:

[0097] (1) 10 parts of PP material and 90 parts of 1,4-addition SEBS material (same as Example 2) were weighed by weight and mixed in a Haake rheometer at a heating temperature of 190° C. for 6 min to obtain a PP-SEBS blend.

[0098] (2) Weigh 0.25 mg of the PP-SEBS blend obtained in step (1) as a sample and place it in a Py-GCMS pyrolysis instrument. The pyrolysis temperature is set to 650°C and the pyrolysis time is 10 s. The chromatographic column model is HP-5MS. The GC heating program is: retain at 40°C for 2 min, heat to 300°C at 20°C / min, and then retain at 300°C for 10 min. The split ratio is 150:1. The interface temperature is 300°C and the front inlet temperature is 300°C. Obtain the pyrolysis mass spectrum and extract the ion chromatograms with m / z 104 and m / z 168 as characteristic ions, as shown in the figure below. Fig.14 and Fig.15 shown.

[0099] from Fig.14 It can be seen that the PP-SEBS blend has an obvious characteristic response of styrene monomer at a retention time of 5.07 min. In addition, in the ion flow chart of m / z 168, the PP-SEBS blend has double peaks at retention times of 7.14 min and 7.67 min. 7.14min / S 7.67min =0.35, which can quickly identify that the material blended with PP is 1,4 addition SEBS, which is consistent with the actual situation.

[0100] Example 7

[0101] This embodiment provides a method for determining a blend of HDPE and PS, comprising the following steps:

[0102] (1) 90 parts of HDPE material (same as in Example 1) and 10 parts of PS material were weighed by weight and mixed in a Haake rheometer at a heating temperature of 190°C for 6 min to obtain a HDPE-PS blend.

[0103] (2) Weigh 0.3 mg of the HDPE-PS blend obtained in step (1) as a sample and place it in a Py-GCMS pyrolysis instrument. The pyrolysis temperature is set to 600°C and the pyrolysis time is 25 s. The chromatographic column model is HP-5MS. The GC heating program is: retain at 40°C for 2 min, heat to 300°C at 20°C / min, and then retain at 300°C for 10 min. The split ratio is 150:1. The interface temperature is 300°C and the front inlet temperature is 300°C. Obtain the pyrolysis mass spectrum and extract the ion chromatograms with m / z 104 and m / z 168 as characteristic ions, as shown in the figure below. Fig.16 and Fig.17 shown.

[0104] from Fig.16 It can be seen that the HDPE-PS blend has an obvious characteristic response of styrene monomer at a retention time of 5.07 min. In addition, in the m / z 168 ion flow chart, the HDPE-PS blend has no peaks at retention times of 7.14 min and 7.67 min, which can quickly identify the material blended with HDPE as PS, which is consistent with the actual situation.

[0105] Comparative Example 1

[0106] Comparative Example 1 refers to the determination method of Example 1, with the only difference being that the sample to be tested prepared in step (1) is different.

[0107] The preparation of the sample of Comparative Example 1 includes: weighing 95 parts of HDPE material (same as Example 1) and 5 parts of 1,2 addition SEBS material (same as Example 1) by weight, kneading and mixing them in a Haake rheometer at a heating temperature of 190° C. for 6 minutes to obtain a HDPE-SEBS blend.

[0108] The ion chromatograms of m / z 104 and m / z 168 were extracted as characteristic ions, respectively. Fig.18 and Fig.19 As shown. Fig.18 It can be seen that the HDPE-SEBS blend has an obvious characteristic response of styrene monomer at a retention time of 5.07 min. In addition, in the m / z168 ion flow diagram, the HDPE-SEBS blend has a peak at a retention time of 7.14 min, and a shoulder peak appears at a retention time of 7.67 min, so S cannot be calculated. 7.14min / S 7.67min , it is not possible to identify whether the material blended with HDPE is 1,2 addition or 1,4 addition SEBS.

[0109] Comparative Example 2

[0110] Comparative Example 2 refers to the determination method of Example 1, with the only difference being that the sample to be tested prepared in step (1) is different.

[0111] The preparation of the sample of Comparative Example 2 includes: weighing HDPE material (same as Example 1), mixing and kneading in a Haake rheometer at a heating temperature of 190° C. for a kneading time of 6 minutes to obtain HDPE.

[0112] The ion chromatograms with m / z 104 and m / z 168 as characteristic ions were extracted, and no characteristic response of styrene monomer appeared in HDPE at the retention time of 5.07min. In addition, in the ion chromatogram of m / z 168, no peaks appeared in HDPE at 7.14min and 7.67min, which indicated that SEBS or PS was not blended in HDPE.

[0113] Comparative Example 3

[0114] Comparative Example 3 refers to the determination method of Example 5, the only difference being that the thermal cracking temperature is different.

[0115] The thermal cracking temperature of Comparative Example 3 is 450°C.

[0116] The ion chromatograms of m / z 104 and m / z 168 were extracted as characteristic ions, respectively. Fig. 20 and Fig.21 As shown. Fig. 20 It can be seen that the PP-SEBS blend has a broad styrene peak at a retention time of 5.12 min, indicating that the polymer is slowly decomposed. In addition, in the m / z 168 ion flow chart, the PP-SEBS blend has no peaks at retention times of 7.14 min and 7.67 min, and it is impossible to identify whether the material blended with PP is SEBS.

[0117] The invention utilizes the cracking principle of styrene polymers with different structures at high temperature and understands the difference in products, and can quickly distinguish the types of polystyrene polymers blended with polyolefins. The method is green, environmentally friendly, accurate and efficient.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for determining styrene polymers in a polyolefin-styrene polymer blend system, characterized in that: The steps include: (a) The blended system sample to be tested was subjected to Py-GCMS test, m / z 104 and m / z 168 were selected as characteristic ions, and the corresponding ion chromatograms were extracted; (b) analyzing and obtaining the type of styrene polymer in the blend system according to the peaks in the ion flow diagram corresponding to m / z 104 and m / z 168; In the test, the thermal cracking temperature is 550°C to 650°C; In the blending system, the mass percentage of the styrene polymer is 10% to 100%; In the blending system, the styrene polymer includes any one of polystyrene and SEBS, and the SEBS includes any one of 1,2 addition SEBS and 1,4 addition SEBS.

2. The measuring method according to claim 1, characterized in that In the blending system, the polyolefin includes at least one of high-density polyethylene, low-density polyethylene, linear low-density polyethylene, metallocene linear low-density polyethylene, polyolefin elastomer and polypropylene.

3. The measuring method according to claim 1, characterized in that In the test, the thermal cracking time is 10s to 30s.

4. The measuring method according to claim 1, characterized in that The test conditions include at least one of the following features: (1) The chromatographic column model is HP-5MS; (2) The split ratio is (100-200):1; (3) Interface temperature is 280℃~300℃, front sample inlet temperature is 280℃~300℃; (4) The GC temperature program was as follows: after holding at 40°C for 2 min, the temperature was increased to 300°C at a rate of 20°C / min, and then held at 300°C for 10 min.

5. The measuring method according to claim 1, characterized in that The mass of the sample is 0.1 mg to 0.5 mg.

6. The measuring method according to any one of claims 1 to 5, characterized in that The analysis includes: when a peak appears at a retention time of 5.07min±0.1min in the ion flow chart of m / z 104, and there are no double peaks at retention times of 7.14min±0.1min and 7.67min±0.1min in the ion flow chart of m / z 168, then the styrene polymer in the blending system is polystyrene.

7. The measuring method according to any one of claims 1 to 5, characterized in that The analysis includes: when a peak appears at a retention time of 5.07min±0.1min in the ion flow diagram of m / z 104, and double peaks at retention times of 7.14min±0.1min and 7.67min±0.1min exist in the ion flow diagram of m / z 168, then the styrene polymer in the blending system is SEBS.

8. The measuring method according to claim 7, characterized in that The analysis also includes: integrating and calculating the peak areas of the ion flow diagram of m / z 168 with retention times of 7.14min±0.1min and 7.67min±0.1min, which are S1 and S2 respectively; when the ratio of S1 to S2 satisfies: 1<S1 / S2<4, the styrene polymer in the blending system is 1,2 addition SEBS; when the ratio of S1 to S2 satisfies: 0.2<S1 / S2<1, the styrene polymer in the blending system is 1,4 addition SEBS.

Citation Information

Patent Citations

  • Analysis method for determining PA66 content in PA66 / PA6 blend by cracking / gas chromatography-mass spectrometry

    CN111413428A

  • Method for determining type of monomer copolymerized with ethylene in polyolefin

    CN117589709A